Pollen analysis: state of the art - Ogden, Gordon (Géographie physique et Quaternaire)

(untitled) (Les Presses de l’Université de Montréal, 1977)
Although nearly 50 years have passed since P.B. Sears introduced pollen analysis to North America, it remains an occult art. Dramatic improvements in sampling and analytic techniques continue to be limited by intractable problems of differential production, dispersal, ballistics, sedimentation, and preservation. It is a basic tenet of pollen stratigraphy that the data set, consisting primarily of microfossils preserved in sediments, is better than anything we have yet been able to do with it. Basic agreement between late- and postglacial pollen records has been confirmed wherever the method has been applied. Quantitative sampling techniques, sample preparation, and analytic procedures, together with multiple radiocarbon dates, permits calculation of sedimentation rates and absolute pollen influx. Of approximately 300 sediment cores from northeastern North America, fewer than 30 have more than 3 radiocarbon determinations from which least squares power curve regressions can be reliably calculated in the determination of sedimentation rates. Analogy with modern environments represented by surface pollen spectra is limited by an insufficient number of samples of uniform quality to characterize a vegetational mosaic covering 40 degrees of latitude (40-80°N) and longitude (60-100°W). The present surface pollen data bank includes about 700 samples, unevenly spaced and of uneven quality, permitting a grid resolution of no better than 10,000 km2.